Teachers and Counselors: Building Math Confidence in Schools - Joseph M. Furner (Lectito Journals, 2017)
Mathematics teachers need to take on the role of counselors in addressing the math anxious in today's math classrooms. This paper looks at the impact math anxiety has on the future of young adults in our high-tech society. Teachers and professional school counselors are encouraged to work together to prevent and reduce math anxiety. It is important that all students feel confident in their ability to do mathematics in an age that relies so heavily on problem solving, technology, science, and mathematics. It really is a school's obligation to see that their students value and feel confident in their ability to do math, because ultimately a child's life: all decisions they will make and careers choices may be determined based on their disposition toward mathematics. This paper raises some interesting questions and provides some strategies (See Appendix A) for teachers and counselors for addressing the issue of math anxiety while discussing the importance of developing mathematically confident young people for a high-tech world of STEM.